Tawarruq: the Islamic perspective and the application in fiqh muamalat / Farah Rabbiah Ahmad … [et al.] - Ahmad, Farah Rabbiah; Adam, Khairunnisa; Parusali, Nurul Izzati; Bahauddin, Siti Nur Sabrina; Jamali, Siti Nurdini (2023)
Fiqh Muamalat is a branch of Fiqh discipline. It is a very vast area of knowledge, yet interesting and challenging. It deals with Shariah rulings related to the area of business and financial activities that rapidly change from time to time in order to meet the changing needs of people and rapid developments throughout the worlds.